Waqf: An Advanced Approach to Combating Agricultural Land Fragmentation in Islamic Countries - Alaa Al-Tulaibawi; Pablo de Frutos Madrazo; Pedro Antonio Martín-Cervantes (World)
This paper addresses the issue of agricultural land fragmentation in Islamic countries. In the se countries, agricultural land is fragmented into tiny and unproductive holdings. Fragmentation of agricultural holdings reduces production due to difficulties in applying modern technology, lack of access to loans, and the challenges in marketing small quantities. The inheritance system, based on Islamic law, is one of the biggest reasons for land fragmentation. Previous complex laws to address land fragmentation often conflicted with national constitutions or Islamic law, making their implementation difficult. A mixed-methods approach was employed, combining qualitative analysis with a one-way analysis of variance (ANOVA) to examine differences in productivity and operational costs per hectare under various land management systems. The findings demonstrate that implementing waqf (endowment) as a land management strategy can significantly mitigate land fragmentation. Waqf preserves agricultural land as a single, indivisible entity, allowing for long-term planning, farm expansion, and sustainable investment. This approach enhances productivity and supports sustainable agricultural development. This study concludes that waqf aligns with Islamic principles and offers a practical, culturally appropriate solution to land fragmentation. By mitigating fragmentation and promoting sustainable development, waqf ensures continuity, supports agricultural growth, and contributes to broader development goals.